UJI COD DAN MIKROBIOLOGI PADA SUMBER MATA AIR NIFUESU DESA BAUMATA UTARA KECAMATAN TAEBENU KABUPATEN KUPANG - Yunita Enjelina Bulu; James Ngginak; Winioliski Rohi Bire (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
Water is a very special chemical compound, which in its content consists of hydrogen compounds (H) and oxygen compounds (O). By Government Regulations No. 82 of 2001 concerning water management, water must meet the criteria of three parameters, namely physical parameters, chemical parameters, and microbiological parameters (Total Coliform). This study aims to determine the water quality in the Nifuesu spring, North Baumata village, Taebenu district, and Kupang regency based on chemical parameters (COD) and Microbiological parameters. The method used is a quantitative descriptive method with an experimental design by comparing the measurement data from each water parameter with the PP quality standard No.82 of 2001. These data show that the COD value at the point I is 7,86 mg/L and point II is 6.13 mg/L. About water quality standards according to PP No.82 of 2001, it can be concluded that the water quality parameters at the location of the Nifuesu spring for COD testing meet the drinking water quality standards set by the Government by the criteria for class I water quality standards 82 of 2001 which is 10 mg/L while the Total Coliformtest at the point I and point II obtained the same results, namely<2400/1000 mL which criteria meet the class II water quality standards set by the Government.Kata Kunci:COD, Mikrobiologi, Sumber Mata Air, NIfuesu